KAJIAN YURIDIS MENGENAI IMPLEMENTASI PENGECUALIAN ASAS MONOGAMI DALAM PERKAWINAN BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DI KOTA TANGERANG (Studi Kasus: Pengadilan Agama Kota Tangerang) - Sri Jaya Lesmana; Fitri Fitri; Alfan Anudatar (Universitas Islam Syekh Yusuf, 2021)
In the rules of law that govern marriage / marriage, there is a recognized sasas which is one of the important ingredients in that line, namely the sasas of smonogamy. Smonogamy is a principle in the line of marriage / marriage in which a man as a husband is not allowed to have more than 1 (one) wife, so on the other hand, a woman as a legal wife can have 1 (one) husband. However, sdi sasas smonogamy in Law Number 1 s of 1974 s Regarding marriage, it provides an exception regarding the sasas, that is, a man can have more than someone else's system if only it is subject to the consent of the first wife. From this background, a problem is obtained, namely how the attitudes of the spouses of the city of Tangerang regarding the principle of monogamy which can be put aside according to Law Number 1 of 1974 s Regarding marriage, as well as what are the constraints, impacts, mechanisms and solutions for implementing the exclusion of the monogamy principle. This research uses normative research methods. The results of this study are the exception to the principle of monogamy as regulated in Law Number 1 of 1974 concerning Marriage, which is a rule that is absorbed from the principles in Islamic Sharia and verified by the state for the implementation of these rules in Indonesia with a mechanism in place. by the state in order to minimize the existence of a polygamy practice that is not covered by positive law in Indonesia, which can result in losses incurred to one of the parties from the existence of this practice. Keywords: Exception, monogamy principle, marriage